Predicting Trait Competitive Anxiety, Competitive Aggression, and Competitive Anger based on Spiritual Intelligence in Veterans and Disabled Athletes - D. Khajavi; H. MirAli (Afarand Scholarly Publishing Institute, 2017)
Aims: In recent years, spirituality has been considered by health professionals as one of the existential dimensions of human beings due to their mental health effects. Spiritual intelligence is also an important factor affecting mental disorders such as anxiety, aggression and anger. Therefore, the purpose of this study was to predict competitive trait anxiety, competitive aggression and competitive anger based on the spiritual intelligence of veterans and disabled athletes. Instrument & Methods: In this descriptive-correlational study in 2016, 80 veteran and disabled athletes from the Arak City, Iran, were selected through available sampling and participated in the study. Demographic characteristics questionnaire, spiritual intelligence questionnaire, competitive anger and aggression inventory and competitive trait anxiety questionnaire. To analyze the collected data, descriptive (mean and percent) and regression statistical tests were used. Findings: There was a significant negative relationship between spiritual intelligence and competitive anxiety (r=-0.22; p<0.05), and spiritual intelligence and competitive anger and aggression (r=-0.27; p<0.05). Spiritual intelligence could predict 4.9% of the variance of competitive anxiety (p=0.048) and 7.0% of the variance of competitive anger and aggression (p=0.017). Conclusion: Spiritual intelligence can reduce competitive anger and anger and competitive aggression in athletes with disabilities and veterans.